The inventory and spore morphology of ferns from Bengkalis Island, Riau Province, Indonesia - Nery Sofiyanti; Mayta Novaliza Isda; ERWINA JULIANTARI; RISSAN SURIATNO; SYAFRONI PRANATA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sofiyanti N, Isda MN, Juliantari E, Pranata S, Suriatno R. 2019. The inventory and spore morphology of ferns from Bengkalis Island, Riau Province, Indonesia. Biodiversitas 20: 3223-3236. Bengkalis Island is one of main islands at coastal region of Riau Province, Indonesia. The first fern inventory had been conducted on this island, to identify the fern checklist as well as examined the morphology of their spores. Samples were collected from 2 subdistricts and 12 study sites, using exploration method. The spore specimens were coated using AU, before observation using Scanning Electron Microscopy (SEM). A total of 22 fern species are recorded from Bengkalis Islands. These species belong to 3 orders, i.e. Gleicheniales (1 species), Polypodiales (20 species) and Schizaeales (1 species). The spore characteristic indicated similar unity of spore, i.e. monad spore, with triangular, subtriangular, tetrahedral and reniform shape. Three basic types of spore have been observed, i.e. monolete, dilete, and trilete. The spore class observed in this study are small (22 ± 0.88 µm), medium (27.35 ± 1.45 to 47.85 ± 0.88 µm) and large (51.34 ± 1.83 to 53.8 ± 1.81 µm). The ornamentation of perisphore is the main character to distinguished species within one genus.